The librarians of Lisbon - Nelson, Suzanne, 1976- (Zando, 2025)
Lisbon 1943. As two American librarians are drawn into a city of dangerous subterfuge and unexpected love affairs, they are forced to choose between their missions and the men they love. Inspired by real historical figures, award-winning author Suzanne Nelson pens a captivating story of two remarkable women, their bravery and heartache, and a friendship that withstands the ravages of war. WWII rages Europe. Lisbon stands alone as a glamorous city on the brink of chaos, harboring spies trading double-edged secrets. Among them are Selene Delmont and Beatrice Sullivan, Boston librarians turned Allied operatives. Officially enlisted to catalog banned books, both women are undercover agents tasked with infiltrating the Axis spy network. Victory is not guaranteed. Soon, they're caught up in games of deception with two of Lisbon's most notorious men--the outcast Portuguese baron, Luca Caldeira, and the lethal spy, code name Gable. As Selene charms her way through lavish ballrooms with Luca, the more bookish Bea is plunged into Gable's shadowy world of informants. But when a betrayal unravels a carefully spun web of lies, everything they've fought for is thrown into jeopardy. As Selene and Bea are pushed to their breaking points can their friendship, and their hearts, survive the cost of war?--